Territorial Displays of the Ctenophorus decresii Complex: A Story of Local Adaptations - Ramos, Jose A.; Peters, Richard A. (Frontiers in Ecology and Evolution, 2021)
Closely related species make for interesting model systems to study the evolution of signaling behavior because they share evolutionary history but have also diverged to the point of reproductive isolation. This means that while they may have some behavioral traits in common, courtesy of a common ancestor, they are also likely to show local adaptations. The Ctenophorus decresii complex is such a system, and comprises six closely related agamid lizard species from Australia: C. decresii, C. fionni, C. mirrityana, C. modestus, C. tjanjalka, and C. vadnappa. In this study, we analyze the motion displays of five members of the C. decresii complex in the context of their respective habitats by comparing signal structure, habitat characteristics and signal contrast between all species. Motor pattern use and the temporal sequence of motor patterns did not differ greatly, but the motion speed distributions generated during the displays were different for all species. There was also variation in the extent to which signals contrasted with plant motion, with C. vadnappa performing better than the other species at all habitats. Overall, this study provides evidence that members of the C. decresii complex exhibit local adaptations in signaling behavior to their respective habitat, but they also maintain some morphological and behavioral traits in common, which is likely a consequence from the ancestral state.